Uncovering the Lack of Public Accountability: An Application of Accounting Standards for Entities in Indonesia - Achyarsyah, Padri; Nur, Muhammad; Indriyanto, Erwin; Digdowiseiso, Kumba; Haat, Mohd Hassan Che (International Journal of Business, Economics & Financial Studies, 2023)
Financial reports hold significant value for all types of business entities, including national and multinational corporations as well as Micro, Small, and Medium Enterprises (MSMEs). Financial reports serve as a means for the report generator to inform interested parties, including the general public, investors, business proprietors, and tax authorities, of transactions that transpire during a specified period. The Indonesian Accounting Association published Accounting Standards for Entities Without Public Accountability (SAK ETAP) to assist start-up enterprises. Consequently, this study aims to investigate the execution of SAK ETAP. A systematic literature review comprises the following phases: formulation of research questions, localization of studies, selection and evaluation of studies, analysis and synthesis, and dissemination of findings via scientific articles. This study concludes that business entities and organizations examined for the implementation of SAK ETAP encompassed various sectors such as pharmacies, Limited Liability Companies (PT), cooperatives (Village Unit Cooperatives – KUD, Savings and Loans Cooperatives – KSP, Republic of Indonesia Employee Cooperatives – KPRI), Commanditaire Vennootschap – CV, People's Credit Bank (BPR), distro, Trading Business (UD), Village-Owned Enterprise (BumDes), Public Fuel Filling Station (SPBU), and Islamic boarding school.